Exploring Strategies to Enhance TVET Engagement in Maldives to Improve Youth Career Development - Sunny, Rahul; Ismail, Affero; Hashim, Mohamed; Naser, Ahmad (Journal of Technical Education and Training, 2023)
Several aspects of the Maldives’ recent development pattern highlight imbalances between labor demand and supply. Public sector jobs are predominantly in the civil service with the rapid expansion of cadres in the 1990s and 2000s. However, with the increasing standard of living over time, the labor market has become more challenging for Maldivians in general. Increasing educational attainment among the younger generation and expectations have coincided/collided with the rapid growth in low-skill service jobs associated with tourism and construction, leading to a mismatch in skills supply and demand. Despite the high levels of growth and labor market conditions in public investments, tourism, fisheries and non-tradable tourism related activities, important challenges remain for young Maldivians. TVET is perceived as second-class option to most of the youth. Many reasons that cloaked these issues such as lack of awareness, publicity and career readiness. This research seeks to identify the issue and challenges and strategies that can be implemented to enhance career development among Maldivian youth on TVET. Mixed method has been adapted in this research by employing questionnaires and conducting interviews. 200 respondents participated in the survey and five experts were involved in the interviews. Data were analysed quantitatively for survey and thematic analysis for the qualitative data. According to the findings, a majority of respondents (81.7%) have heard of Technical and Vocational Education and Training (TVET), but less than half (45.2%) understand that it can lead to better employment opportunities. Experts have identified seven strategies to improve TVET for youth career development, including promoting it through electronic media, launching a national campaign, strengthening partnerships with industry, branding and holding skills competitions. This information is valuable for policymakers and stakeholders in the Maldives as they work to design and implement effective and coordinated government support for TVET.